Contents of diterpenes in espresso coffee brews prepared from commercial capsules - Wuerges, Karla Leticia; Santos, Ana Carolina Forgati dos; Mori, André Luiz Buzzo; Benassi, Marta de Toledo (Coffee Science - ISSN 1984-3909, 2016)
The objective of this work was to quantify kahweol and cafestol diterpenes in coffee brews prepared from commercial capsules for espresso in the Brazilian market. Four types of brews, with five preparation replications, were evaluated. The capsules had differences in the amount and type of roasted and ground coffees used (blends of arabica and robusta coffee or 100% arabica coffee), and in the conditions of time and volume of extraction (dose) recommended by the manufacturer. The coffee brews presented 1.42 and 4.88 g of solids/100 mL. Concentration of solids decreased with the increase in time/volume extraction. Contents of 0.47 to 1.04 mg of kahweol and 0.38 to 0.92 mg of cafestol by dose (ranging from 35 to 120 mL) were observed. These contents corresponded to a range of 0.40 to 2.96 mg of kahweol/100 mL and 0.32 to 2.62 mg of cafestol/100 mL. The fraction of diterpenes extracted varied from 1.85 to 4.27 % for kahweol and 1.87 to 4.16 % for cafestol. Considering the contents of cafestol, there is no indication of a hypercholesterolemic effect due to a moderate consumption of coffee brews prepared from these commercial capsules.